Penerapan Sistem FIFO (First In First Out) dalam Menjamin Konsistensi Kualitas Produk Pengolahan Pangan di Dapur Makan Bergizi Gratis Wilayah Warungdowo Kabupaten Pasuruan - Chaizurrohman, Mokhammad Mahbub; Sulistiyawati, Anik (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The Free Nutritious Meal Program (MBG) is one of the government’s strategic initiatives aimed at improving the nutritional status of the community, particularly among school-aged children. The food ingredients used in MBG kitchens are generally perishable in nature, thus requiring an appropriate stock management system to prevent waste and quality degradation. One of the widely recognized stock management methods in the food and logistics industry is the First In First Out (FIFO) method. This research is a quantitative descriptive study using a field study (case study) approach. Based on the results, the implementation of the First In First Out (FIFO) system plays a crucial role in maintaining the consistency of food product quality in the Free Nutritious Meal (MBG) kitchen. The FIFO system has proven effective in ensuring that food ingredients entering the storage area first are used first, thereby minimizing the risk of quality deterioration and ingredient expiration.